WANPRESTASI YANG DILAKUKAN OLEH PEMILIK LAHAN DALAM PERJANJIAN SEWA MENYEWA LAHAN - Trisna Dewi Ni Made (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Disputes that occur in land lease agreements can be due to various factors, including the result of parties to the agreement who have defaulted. The formulation of the problem raised in this study is how the legal protection for tenants due to default by the land owner and how legal remedies can be taken by tenants due to default by the land owner. This type of research is normative legal research. The conclusion of this research is that legal protection for tenants due to default by the land owner is if the land owner and the tenant make an agreement at a notary and explain that they have entered into an agreement and ask the notary to make a deed, then this deed is a deed made before a Notary (Deed of Notarial), the parties to the agreement have legal certainty and are therefore legally protected, so that if a dispute occurs in the implementation of the agreement, the judge with his decision can force the violating party to exercise his rights and obligations in accordance with the agreement. . Legal remedies that can be taken by tenants as a result of default by the land owner. Parties who feel that they are disadvantaged due to default can demand fulfillment of the agreement, cancel the agreement or ask for compensation from the party who did the default.